Protecting Consumers from Motorcycle Users with Non-Standard Motorcycle Iron Frames - Rahayu, Rika (Sharia and Law Faculty, 2024)
In the era of globalization like today, especially in big cities that are often affected by traffic jams, motorcycles can be used as an alternative in supporting transportation facilities and infrastructure on the highway. Nowadays consumers always ignore the importance of a good and standard motorcycle frame. This problem has become familiar throughout Indonesia, without denying that consumers prioritize trends or styles in riding motorcycles. Of course, this is very contrary to the mandate of the Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 12 of 2019. This research is an empirical juridical legal research with a statute approach, namely research or observation in the field or field research whose research focuses on collecting empirical data in the field. The results of this study state that (1) if the purchase of a motorcycle is damaged due to modifications that violate existing laws and regulations such as replacing the iron frame of the motorcycle is not in accordance with the standard value, the company has no responsibility for this incident, if the consumer deliberately modifies the motorcycle and 2) the consumer related to his actions that violate the regulations, namely modifying with an iron frame that is not in accordance with the standard then Penalties are imposed in the form of fines and coaching for related perpetrators, especially guidance on knowledge related to the dangers of using modified motorcycles that are not in accordance with standards and summons to parents related to follow-up mediation and the letter of agreement will not repeat the act.